Clinical outcome after endovascular thrombectomy in 3 triage concepts: a prospective, observational study (NEUROSQUAD) - Seker, Fatih; Fiehler, Jens; Möhlenbruch, Markus Alfred; Herweh, Christian; Flottmann, Fabian; Ringleb, Peter A.; Thomalla, Götz; Steiner, Thorsten; Kraemer, Christoffer; Brekenfeld, Caspar; Bendszus, Martin (Stroke, 2021)
Background and Purpose: - - NEUROSQUAD (Stroke Treatment: Quality and Efficacy in Different Referral Systems) is a prospective, observational, bicenter study comparing 3 triage pathways in endovascular stroke treatment: mothership, drip and ship (DS), and transferring a neurointerventionalist to a remote hospital for thrombectomy (drive the doctor [DD]). - - Methods: - - Patients with anterior circulation stroke and premorbid modified Rankin Scale (mRS) score 0-3 who underwent thrombectomy within 24 hours after stroke onset were included. Primary outcome measure was good clinical outcome defined as 90-day mRS score 0-2 or clinical recovery to the status before stroke onset (ie, equal premorbid mRS and 90-day mRS). Secondary outcome measures were successful reperfusion, National Institutes of Health Stroke Scale at discharge, and mRS shift. - - Results: - - In total, 360 patients were included in this study, of whom 111 patients (30.8%) were in the mothership group, 204 patients (56.7%) were in the DS group, and 45 patients (12.5%) were in the DD group. Good clinical outcome was achieved similarly in all three groups (mothership, 45.9%; DS, 43.1%; DD, 40.0%; P=0.778). Likewise, frequency of successful reperfusion was similar in all three groups (mothership, 86.5%; DS, 85.3%; DD, 82.2%; P=0.714). There was no significant difference among the groups regarding the National Institutes of Health Stroke Scale at discharge (P=0.115) and mRS shift (P=0.342). In the multivariate analysis, triage concept was not an independent predictor of good outcome (unadjusted odds ratio, 0.89 [CI, 0.64-1.23]; P=0.479). - - Conclusions: - - Our data suggest that clinical outcome after thrombectomy is similar in mothership, DS, and DD. Hence, DD can be a valuable triage option in acute stroke treatment.